2020
DOI: 10.1364/ol.386267
|View full text |Cite
|
Sign up to set email alerts
|

Impact of laser flicker noise and linewidth on 64 to 96  Gbaud/DP-nQAM metro coherent optical links

Abstract: We experimentally investigate the impact of laser flicker noise and linewidth on 64 Gbaud/DP-64QAM, 96 Gbaud/DP-32QAM and 64 or 96 Gbaud/DP-16QAM links. To give a more practical viewpoint, the examined flicker noise closely follows that of an industry forum (OIF 400ZR). We have found that higher modulation order (e.g., 64QAM) is sensitive to phase noise from the linewidth and flicker noise, even in the back to back case. Significant optical signal to noise ratio (OSNR) and cycle slip rate penalties can also be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In many specific applications, the laser is also required to maintain a long-term single-frequency operation without frequency hopping; meanwhile, phase noise should be minimized. 34,35 Therefore, to fulfill the requirements of different applications, it is necessary to understand the properties of different types of narrow-linewidth lasers and their output parameters. This section summarizes several representative approaches to narrow-linewidth lasers.…”
Section: Approaches Toward Narrow-linewidth Lasersmentioning
confidence: 99%
See 1 more Smart Citation
“…In many specific applications, the laser is also required to maintain a long-term single-frequency operation without frequency hopping; meanwhile, phase noise should be minimized. 34,35 Therefore, to fulfill the requirements of different applications, it is necessary to understand the properties of different types of narrow-linewidth lasers and their output parameters. This section summarizes several representative approaches to narrow-linewidth lasers.…”
Section: Approaches Toward Narrow-linewidth Lasersmentioning
confidence: 99%
“…In general, an SLM laser is assumed to be a single‐frequency laser if its linewidth is narrower than the resolution of a spectrum analyzer or the nonlinear gain bandwidth of a specific medium. In many specific applications, the laser is also required to maintain a long‐term single‐frequency operation without frequency hopping; meanwhile, phase noise should be minimized 34,35 . Therefore, to fulfill the requirements of different applications, it is necessary to understand the properties of different types of narrow‐linewidth lasers and their output parameters.…”
Section: Approaches Toward Narrow‐linewidth Lasersmentioning
confidence: 99%
“…Distortions from EEPN will result in a significant degradation of the system performance. Tremendous investigations with EEPN have been carried out for linear optical transmission systems 7,[14][15][16][17][18][19][20][21][22] . It is indicated that the EEPN, a source of severe performance degradation in long-haul transmission systems, increases with the accumulated CD, local oscillator (LO) laser linewidth, the modulation format and the symbol rate of the system 7,15,19 .…”
Section: Introductionmentioning
confidence: 99%